Are young university millennials compulsive in their purchase? - Fischer-De la Vega, Laura Estela; Espejo-Callado, Jorge Ángel (Horizonte Sanitario, 2018)
Objective: To analyze the purchasing behaviors in university students of the Mexican Republic and determine if there are differences between sexesthat show the behavior provided is considered compulsive, following the model of Valence, d'Astous and Fortier.Materials and methods: We carried out a quantitative, descriptive, correlational and explanatory study, because it confirms the structure of theValence d'Astous and Fortier compulsive buying scale, in the following factors: tendency to spend, reactive aspect and post-purchase guilt. The studyinvolved 1,687 students of the millennials generation of 27 states of the Mexican Republic, composed of a 60 per cent of women and 40% men; thedata collection was made via online with the software SurveyMonkey using a questionnaire of 16 items, in Likert scale. The statistical treatment usedwas the Pearson’s Chi-square test, by the SPSS version 24.Results: The findings show that the purchasing behavior of the sample under study cannot be considered as compulsive disorder under the model ofValence, d'Astous And Fortier, although women in relation to men, had a tendency toward compulsive buying, this got on the results shown in theconstruct "tendency to spend".Conclusions: The results obtained by this research must be of great importance for companies; it is important to note that the subject of the compulsivebuying should be a concern and the subject of further research for universities, authorities and practitioners of marketing. Today, thanks to studies onthe subject, responsibles for developing the marketing strategies are becoming more aware of how they affect the decisions of consumers, we must notlose sight of the fact that the members of the millennial generation are the future of the country and the world, and they should have the opportunity tomake more responsible consumption, of benefit to the current world and future generations.